Evaluating Activated Carbon Dopped PVA/Starch Membrane as a Tissue Patch - Yildirim, Meryem Akkurt; Celikkaya, Neslisah; Denktas, Cenk (WILEY, 2025)
Polyvinyl alcohol (PVA) and starch (St) are recognized as promising materials for developing artificial tissues. This study doped PVA/St composites with activated carbon (AC) and crosslinked by tannic acid. The effects of carbon concentrations on PVA/St composites were investigated in terms of changes in morphological, thermal, mechanical, swelling, and biological behaviors. The utilization of AC-doped PVA/St membranes as tissue patches were evaluated. The Young's Modulus [Ey (MPa), %22, 53] and tensile strength [sigma T(MPa), %28, 28] of AC doped PVA/St membranes were decreased due to the entanglement between the chains and, the brittleness of the composite increased. The FTIR analysis revealed that the hydrogen bond density and thermal stability increased. The hydrophobicity of all samples ranged from 75.35 degrees to 65.52 degrees. The hydrophobicity of the membranes was determined between 75.35 degrees and 65.52 degrees. It was determined that PVA/starch tissue patches with different ratios of AC did not present any toxic effects on the L929 fibroblast cell line. Besides, AC has been found to increase cell viability. The cell adhesion decreased by 1%-7% with the increase amount of AC. The incorporation of AC into PVA/St composites has been found to increase oxidant levels while decreasing antioxidant activity.
Keywords: activated carbon; biocompatibility; mechanical behavior; tissue patch; POLYVINYL-ALCOHOL; POLY(VINYL ALCOHOL); HYDROGEL MEMBRANES; CELL-CULTURE; COMPOSITES; NANOCOMPOSITES; GENERATION; SCAFFOLDS; FILM; PVA; Polymer Science